1998
DOI: 10.1177/1045389x9800900205
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Pseudoelastic Hysteresis Damping Characteristics of Shape Memory Alloy Wires

Abstract: An experimental investigation was conducted to determine the pseudoelastic hysteresis damping characteristics of Ni-Ti Shape Memory Alloy (SMA) wires. The comprehensive study examines the effects of cycling, oscillation frequency, strain amplitude, temperature, and static strain offset on the pseudoelastic stress-strain hysteresis of SMA wires under axial loading. Experimental data are obtained for complete austenite-martensite transformation hysteresis as well as partial transformation hysteresis. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 7 publications
7
58
0
Order By: Relevance
“…Concerning the strain rate at which fatigue takes place, up to now cycling research of NiTi SMAs has focused on tensile behavior at low strain rates, from 10 −4 to 10 −3 s −1 . The cyclic characterization for higher strain rates has been carried out by a few groups, mostly limited to the order of 10 −1 s −1 [3,12,13]. Higher strain rates, on the order of 10 3 s −1 , have recently been achieved using Split Hopkinson Pressure Bar technique (S.H.P.B.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the strain rate at which fatigue takes place, up to now cycling research of NiTi SMAs has focused on tensile behavior at low strain rates, from 10 −4 to 10 −3 s −1 . The cyclic characterization for higher strain rates has been carried out by a few groups, mostly limited to the order of 10 −1 s −1 [3,12,13]. Higher strain rates, on the order of 10 3 s −1 , have recently been achieved using Split Hopkinson Pressure Bar technique (S.H.P.B.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent research, it has been found that the properties of the SE depend on cyclic loading [6][7][8], strain rate [9][10][11][12] and the loading conditions [13][14][15]. In order to design SMA elements in Science which the properties of energy storage and dissipation due to the SE are used, it is important to evaluate these properties properly and to take them into account of the design.…”
Section: Introductionmentioning
confidence: 99%
“…The complex modulus is widely used in the fields of elastomers and hysteretic elements in general [28]. The advantage of using the complex modulus is that the relatively complicated SMA behaviour can be simplified into a single quantity having a real and an imaginary part that may be functions of e.g.…”
Section: Complex Modulusmentioning
confidence: 99%